2013
DOI: 10.3390/en6094607
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environmental Factors and Nutrient Availability on the Biochemical Composition of Algae for Biofuels Production: A Review

Abstract: Due to significant lipid and carbohydrate production as well as other useful properties such as high production of useful biomolecular substrates (e.g., lipids) and the ability to grow using non-potable water sources, algae are being explored as a potential high-yield feedstock for biofuels production. In both natural and engineered systems, algae can be exposed to a variety of environmental conditions that affect growth rate and cellular composition. With respect to the latter, the amount of carbon fixed in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
271
1
31

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 686 publications
(337 citation statements)
references
References 215 publications
(261 reference statements)
7
271
1
31
Order By: Relevance
“…The stress condition triggered due to the nutrient content of nitrogen and phosphorus as both a particular key for protein and lipid accumulation in microalgae cells. It is likely known that the aspects of this stress conditions are tightly linked to the available amount of nutrients; limitation of nitrogen, phosphorus, and the presence of other microorganisms [18]. Moreover, the trend value of protein and lipid were similar to the values reported by Markou et al [19] who cultivated microalgae using slaughterhouse wastewater and revealed that this phenomenon could be explained to …”
Section: Fig 1 Protein and Lipid Contentsupporting
confidence: 73%
“…The stress condition triggered due to the nutrient content of nitrogen and phosphorus as both a particular key for protein and lipid accumulation in microalgae cells. It is likely known that the aspects of this stress conditions are tightly linked to the available amount of nutrients; limitation of nitrogen, phosphorus, and the presence of other microorganisms [18]. Moreover, the trend value of protein and lipid were similar to the values reported by Markou et al [19] who cultivated microalgae using slaughterhouse wastewater and revealed that this phenomenon could be explained to …”
Section: Fig 1 Protein and Lipid Contentsupporting
confidence: 73%
“…The quantity and quality of fatty acids content as well as the entire biochemical composition varies in response to environmental conditions 8,20,24,25,38,39 . Particularly, under unfavorable environmental or stress conditions for growth, such as salinity, temperature, pH, and nutrient levels, many algae alter their lipid biosynthetic pathways towards the formation and accumulation of neutral lipids to control intracellular stress 13,40 .…”
Section: Discussionmentioning
confidence: 99%
“…PUFAs are one of the most nutritionally important and essential fatty acids because they are key nutrients in animal nutrition, and the most algae are rich in these acids 43 . Nitrogen and phosphate are two important macronutrients for phospholipids because nitrogen and phosphorus starvation shifts the lipid metabolism from membrane lipid synthesis to neutral lipid storage 39,[44][45][46] . Results of the present study also showed clearly that peaks in PUFAs are related to nitrogen and phosphorus, but its correlation with potassium and magnesium was more evident.…”
Section: Discussionmentioning
confidence: 99%
“…An identical analysis using DM data showed similar performance to AFDM, but higher B max values. This can be explained by inorganic matter in the samples [2,54].…”
Section: Effect Of Velocity On Biomassmentioning
confidence: 99%